2021
DOI: 10.1111/cas.14886
|View full text |Cite
|
Sign up to set email alerts
|

Safety and antitumor activity of acalabrutinib for relapsed/refractory B‐cell malignancies: A Japanese phase I study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Rash, diarrhea, headache, nausea, fatigue, and myalgia have been reported for other second-generation BTK inhibitors [32][33][34]. In earlier studies, rash, diarrhea, headache, nausea, fatigue, and myalgia were reported in up to 33%, 58%, 69%, 27%, 21%, and 38% of patients in clinical trials of acalabrutinib [35,36].…”
Section: Discussionmentioning
confidence: 86%
“…Rash, diarrhea, headache, nausea, fatigue, and myalgia have been reported for other second-generation BTK inhibitors [32][33][34]. In earlier studies, rash, diarrhea, headache, nausea, fatigue, and myalgia were reported in up to 33%, 58%, 69%, 27%, 21%, and 38% of patients in clinical trials of acalabrutinib [35,36].…”
Section: Discussionmentioning
confidence: 86%
“…However, we did identify six clinical trials that reported the occurrence of TLS while on acalabrutinib for management of CLL/SLL (Table 3). [58][59][60][61][62][63] Four of the six trials involved acalabrutinib monotherapy whereas two studies involved multitherapy with obinutuzumab or venetoclax. The mean age of patients was 65.1 years and 68% were male.…”
Section: Acalabrutinibmentioning
confidence: 99%
“…The dose of acalabrutinib ranged from 100 to 200 mg daily. Four nonfatal TLS cases were reported with two during monotherapy 58,62 and two on multiagent therapy. 59,63 None of these studies used TLS prophylaxis.…”
Section: Acalabrutinibmentioning
confidence: 99%